Konsep Pendidikan Islam dan Perkembangannya dalam Menghadapi Problem Pendidikan - Siti Makhmudah (Tafhim Al-'Ilmi, 2020)
Islamic education is education that is conscious and purposeful, God hasestablished a clear educational foundation for all humans through Islamic law.The concept of education in Islam is, First, Education is an activity that must haveclear goals, objectives and targets. Second,The true and absolute educator is Allah SWT, He is the Creator of nature, theGiver of talent, the Maker of various sunnah developments, enhancements, andinteractions of nature as He also prescribes the rules in order to realize theperfection, benefit and happiness of the nature. Third, education demands therealization of a tiered program through increased education and teachingactivities in line with children's development. Fourth, the role of an educator mustbe in accordance with the purpose of AllahSWT creating it